Hairy Maclary from Donaldson's dairy - Dodd, Lynley (London : Puffin, 1995)
A small black dog and his canine friends are terrorized by the local tomcat.
Keywords: Cats -- Fiction; Dogs -- Fiction; Stories in rhyme